Az erdélyi magyar felekezeti oktatási intézmények helyzetének fő vonásai az 1920-as években - Sarnyai, Csaba Máté (Közép-Európai Közlemények, 2015)
Within its territory, which had been extended by the peace treaties following WW1, Romania intended to create a nation-state that is also religiously uniform. Therefore, minorities in Transylvania meant a twofold problem, as they were both Hungarians and Roman Catholics. Just as Romanians had the denominational schools as fountainheads of national/ethnic awakening during Hungarian authority, now these schools served the safekeeping of the Hungarian national sentiment. This is why governments strived to suppress them as much as possible, even if they were obliged by international treaties to protect them. With regard to governmental actions and public attitude, four periods can be distinguished. In our paper, we aim at monitoring and evaluating the process in an analytic manner.